2019
DOI: 10.1016/j.jallcom.2018.08.032
|View full text |Cite
|
Sign up to set email alerts
|

On the prediction and the formation of the sigma phase in CrMnCoFeNix high entropy alloys

Abstract: The almost limitless variations in potential compositions of high entropy alloys necessitates the use of computational methods when attempting to optimise for any given application. However, the accuracy of the current thermodynamic approaches commonly being used for this purpose remains under debate, as relatively few validatory studies have been performed. Within the CrMnFeCoNi family of alloys, the formation of the phase and how it is influenced by compositional variations is of particular interest for elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…THERMOCALC software version 2018 (Thermo-Calc Software AB, Solna, Sweden) was used to calculate the phase composition prediction. Unfortunately, the currently developed HEA database (TCHEA1) could not be used as it does not involve interstitial elements, and its accuracy was questioned [ 16 ]. As such, THERMOCALC calculations were realized using an Ni-based alloy database (TCNI9) instead.…”
Section: Methodsmentioning
confidence: 99%
“…THERMOCALC software version 2018 (Thermo-Calc Software AB, Solna, Sweden) was used to calculate the phase composition prediction. Unfortunately, the currently developed HEA database (TCHEA1) could not be used as it does not involve interstitial elements, and its accuracy was questioned [ 16 ]. As such, THERMOCALC calculations were realized using an Ni-based alloy database (TCNI9) instead.…”
Section: Methodsmentioning
confidence: 99%
“…One such approach is the CALPHAD method [25], which has proven highly effective in more conventional alloy systems. However, the underpinning thermodynamic databases are predominantly based on the phase equilibria of binary and, to a lesser extent, ternary systems and an increasing body of evidence shows that the fidelity of their predictions in higher order systems, particularly at near-equiatomic compositions, is unreliable [18,[26][27][28][29][30][31]. Furthermore, many studies of phase stability in HEAs have focused on temperatures in excess of 1000˚C [18,28,30], where single-phase solid solutions are more likely to form due to the enhanced entropic contribution to Gibbs energy.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true when investigating phase stability at low homologous temperatures, where there may be severe kinetic limitations to phase formation, as evidenced in recent radiotracer studies [33][34][35]. So far, comparisons of CALPHAD predictions, using the TCHEA1 database, with experimental results have shown that the calculations significantly underestimate the temperature range of stability of the phase [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations